The One Health for Environmental Literacy in a Changing World - Özbaş, Cansu; TOPRAK, Şahin; GÜLTEKİN KOÇ, Esra; Serkan , Serkan; AKDOĞAN, Ahmet; VELOSO, Jorge; MOLINARI, Antonio; ALTUNSOY, Mustafa; ÖZKAN, Seçil (Turkey Health Literacy Journal, 2025)
This project aimed to enhance environmental health literacy (EHL) and green skills among adults through the integration of the One Health approach, which emphasizes the interconnections between human, animal, and ecosystem health. A mixed set of activities was implemented across Italy, Portugal, and Turkey, including five project meetings, partnership workshops, and training programs. A Trainers’ Training Program in Portugal brought together 24 experts, while adult training sessions reached 130 participants from diverse backgrounds. Educational outputs included trainer and participant guides, as well as a survey implementation and evaluation report. Promotional activities were conducted in all partner countries to disseminate project results. The project also organized three tree planting and plant ownership activities, strengthening environmental responsibility and sustainability awareness. A multisectoral workshop in Italy with 16 participants fostered cross-sectoral dialogue and collaboration. Additionally, the official EnvirONE-HEALTH website and e-learning platform were launched to provide resources, training materials, and communication tools. The One Health Environment Open Platform, integrated within the website, further supported engagement through resources, a chat function, and an EHL survey. Overall, the project significantly contributed to improving EHL, promoting green skills, and fostering interdisciplinary cooperation for sustainable health outcomes.
Keywords: Enviorenmantal issues; Health; Environmental health; Environmental health literacy